Burning Stone Village Football Club (BSV FC) Information Management System - Hamimma Faradilla; Yana Mazwin Mohmad Hassim (Applied Information Technology And Computer Science, 2023)
Football club management system is used to manage the information of the teams, matches, and performances of the football club. Currently, some football club still implement the manual record management system to store the records of managers, coach, players, training and match performance, and records of the matches. This football club management system aims to administer and manage the information of Burning Stone Village Football Club (BSV FC) systematically and effectively. The modules in this system include homepage information, personal details, performance, match, and report modules. The system is developed using structural approach and prototype model. PHP and MySQL are the coding languages used in this project. By using this system, the management of the football club’s information may be easier and more organized.